Effect of foliar application of nano-nutrients on yield attributes and quality of groundnut (Arachis hypogaea L.) under guava based agri-horti system: EFFECT OF FOLIAR APPLICATION ON YIELD ATTRIBUTES AND QUALITY OF GROUNDNUT - KHUMITA VERMA,; R N MEENA,; P HALESHA,; LAKEY RADHA, (Journal of Oilseeds Research, 2025)
The experiment was conducted at Agricultural Research Farm, Rajiv Gandhi South Campus, Banaras Hindu University, Barkachha, Mirzapur district of Uttar Pradesh during the kharif season of 2022-2023 to study the effect of foliar application of nano-nutrients on yield attributes and quality of groundnut under guava based agri-horti system. The experiment was laid out in randomized block design in which total 12 treatments were randomly allocated and replicated thrice viz., control spray water only (T1), foliar application of Nano Mo 5 % (T2), foliar application of Nano B 10 % (T3), foliar application of Nano Zn 0.5 % (T4), foliar application of Nano Mo + B (T5), foliar application of Nano Mo + B + Zn (T6), fertigation of Urea + Foliar application of water (T7), fertigation of Urea + Foliar application of Nano Mo (T8), fertigation of Urea + Foliar application of Nano B (T9), fertigation of Urea + Foliar application of Nano Zn (T10), fertigation of Urea + Foliar application of Nano Mo + B (T11) and fertigation of Urea + Foliar application of Nano Mo + B + Zn (T12). The findings of the present experiment revealed that the treatment T12 consisting of fertigation of urea in combination with foliar spray of nano (Mo+B+Zn) recorded significantly higher growth parameters, yield attributing parameters, seed yield (1.96 t/ha), kernel yield (1918.20 kg/ha), seed quality parameters along with significantly improved the soil quality which eventually transformed into significantly higher gross returns of ` 153456.00, net returns of ` 109741.00 along with B:C of 2.51. Thus, hereby, it is recommended to the farmers of eastern Uttar Pradesh region to practice application of urea through fertigation combined with foliar application of essential nano-micronutrients (Mo, B and Zn) for generating significantly higher income through cultivation of major oilseed groundnut.